Floristic analyses of Shandong peninsula and adjacent areas indicate the barrier effect of the Yellow river on floristic diversity - Wang, Suyin; Xian, Qing; Yang, Liu; Zhang, Wei (Frontiers in Plant Science, 2024)
The Shandong Peninsula, the largest peninsula in China, is situated at the estuary of the Yellow River and is bordered by both the Bohai Sea and the Yellow Sea. This region is renowned for its rich plant diversity. However, the historical origins of these plant species remain poorly understood. This study analyzed 2410 shared species from 865 genera and 161 families distributed across Shandong and its nine adjacent regions to investigate the floristic diversity of the Shandong Peninsula. These regions were considered as operational taxonomic units (OTUs), with the shared species serving as the basis for each OTU. Hierarchical cluster analyses were performed to assess their floristic similarity, employing the Bray-Curtis distance algorithm and the UPGMA clustering method. The results revealed that the ten regions were grouped into three clusters, delineated by the Yellow River. Notably, the floristic similarity of the Shandong Peninsula was found to be more closely aligned with regions south of the Yellow River, despite Shandong historical connection to Liaoning in the north. These findings underscore the barrier effect of the Yellow River and provide insights into the formation of biotic diversity patterns between northern and eastern China.